Bisnis Sosial: Sintesis Muhammad Yunus untuk Menggerakkan Kapitalisme di Bangladesh - Rizky, Lucitania (Jurnal Hubungan Internasional, 2015)
The emerge of Social Business offers a new kind of capitalism in some developing countries. This manifestation of capitalism concept has introduced by Muhammad Yunus as a respond to vicious cycle poverty in Bangladesh. Grameen Bank has been creating a solid relation between capitalism and poverty. By using the people center development perspective and sustainable development concept, this article tries to elaborate the friendly of capitalism pattern to the poor and its development agenda. This article assured that the relation development.